Design of A Floodgate System Based on Hydropower Generation (PLTA) to Prevent Flooding - Wahyu Imam; Rendi Novendra (International Research & Development for Human Beings (IRDH), 2025)
Global climate change and increasing rainfall intensity have significantly heightened the risk of flooding, particularly in vulnerable areas. To address this issue, this research aims to develop an automatic floodgate system powered by hydropower as a sustainable solution for flood disaster mitigation. The system utilizes hydraulic energy from river or canal flows to drive a micro-hydro generator, which supplies electricity to operate a sluice gate actuator. Water level sensors are deployed to monitor real-time water surface fluctuations and relay data to a controller that autonomously regulates the floodgate operation. The research employed a combination of hydropower generation, real-time sensor integration, and automated control systems to achieve the desired functionality. Testing demonstrated that the system effectively responds to varying water levels, ensuring precise water flow regulation and reducing flood risks. The results highlight the system's efficiency and sustainability, offering an environmentally friendly and self-contained method for flood control. This solution presents a scalable approach to protecting communities from potential flood damage while promoting energy independence.